Variations in Thalamic Anatomy Affect Targeting in Deep Brain Stimulation for Epilepsy - Wu, Chengyuan (Stereotact Funct Neurosurg, 2016)
BACKGROUND: Thalamic size and shape vary significantly across patients – with changes specific to the anterior thalamus occurring with age and in the setting of chronic epilepsy. Such ambiguity raises concerns regarding electrode position and potential implications for seizure outcomes. METHODS: MRIs from six patients from a single center underwent quantitative analysis. In addition to direct measurements from post-implantation MRIs, the CRAnialVault Explorer suite was used to normalize electrode position to a common reference system. Relationships between thalamic dimensions, electrode location, and seizure outcome were analyzed. RESULTS: Although this study group was too small to sufficiently power statistical analysis, general trends were identified. There was a trend towards smaller thalamic volumes in non-responders. Electrode locations demonstrated more variation after normalization. There was a trend towards a more lateral, posterior, and inferior electrode position in non-responders. CONCLUSIONS: Variations in thalamic shape and volume necessitate direct targeting. Given changes that occur to thalamic anatomy with age and in the setting of epilepsy, improved methods for visualizing and targeting the anterior nucleus are necessary. Pronounced thalamic atrophy may preclude proper electrode placement and serve as a poor prognostic indicator. A greater understanding of thalamic anatomy and connectivity are necessary to optimize DBS for epilepsy.